Magnetic field direction differentially impacts the growth of different cell types. (3rd April 2018) - Tian, Xiaofei; Wang, Dongmei; Zha, Meng; Yang, Xingxing; Ji, Xinmiao; Zhang, Lei; Zhang, Xin
ABSTRACT: Magnetic resonance imaging (MRI) machines have horizontal or upright static magnetic field (SMF) of 0.1–3 T (Tesla) at sites of patients and operators, but the biological effects of these SMFs still remain elusive. We examined 12 different cell lines, including 5 human solid tumor cell lines, 2 human leukemia cell lines and 4 human non-cancer cell lines, as well as the Chinese hamster ovary cell line. Permanent magnets were used to provide 0.2–1 T SMFs with different magnetic field directions. We found that an upward magnetic field of 0.2–1 T could effectively reduce the cell numbers of all human solid tumor cell lines we tested, but a downward magnetic field mostly had no statistically significant effect. However, the leukemia cells in suspension, which do not have shape-induced anisotropy, were inhibited by both upward and downward magnetic fields. In contrast, the cell numbers of most non-cancer cells were not affected by magnetic fields of all directions. Moreover, the upward magnetic field inhibited GIST-T1 tumor growth in nude mice by 19.3% ( p  < 0.05) while the downward magnetic field did not produce significant effect. In conclusion, although still lack of mechanistical insights, our results show that different magnetic field directions produce divergent effects on cancer cell numbers as well as tumor growth in mice. This not only verified the safety of SMF exposure related to current MRI machines but also revealed the possible antitumor potential of magnetic field with an upward direction.